Development of a Stitched Monolithic Pixel Sensor prototype (MOSS chip) towards the ITS3 upgrade of the ALICE Inner Tracking system. (1st January 2023) - Vicente Leitao, P.; Aglieri Rinella, G.; Bugiel, S.; Cecconi, L.; de Melo, J.L.A.; De Robertis, G.; Deng, W.; Dorda Martin, A.; Dorosz, P.; Fang, X.; Gajanana, D.; Gromov, V.; et al.
Abstract: The MOnolithic Stitched Sensor (MOSS) is a development prototype chip towards the ITS3 vertexing detector for the ALICE experiment at the LHC. Designed using a 65 nm CMOS Imaging technology, it aims at profiting from the stitching technique to construct a single-die monolithic pixel detector of 1.4 cm × 26 cm. The MOSS prototype is one of the prototypes developed within the CERN-EP R&D framework to learn how to make stitched wafer-scale sensors with satisfactory yield. This contribution will describe some of the design challenges of a stitched pixel sensor and the techniques adopted during the development of this prototype.